Prognostic factors and treatment outcomes in pediatric autoimmune encephalitis: a multicenter study - Abu Melha, Ahlam Ahmed; Aldress, Amjad Saad; Alamri, Fahad; Aljomah, Lama Saleh; Hommady, Raid; Al-Rumayyan, Ahmed; Albassam, Fahad (Frontiers in Neurology, 2024)
emergence of additional immunotherapy agents (i.e., tocilizumab and bortezomib). In this retrospective observational study of pediatric AE conducted at two tertiary care centers, we observed the clinical characteristics, autoantibody yield, treatment modalities used, and disability scores during presentation and follow-up. Our secondary aim was to delineate prognostic factors for poor outcomes. Neuropsychiatric symptoms, encephalopathy, and seizures were the predominant manifestations in most of our patients. Younger age groups, refractory seizures, profound encephalopathy, and refractory disease harbored higher disability scores. The group that received combined immunotherapy has shown mitigation of disability score from severe to mild during longterm follow-up, signifying the role of multifaceted immunotherapy in pediatric refractory AE.